2002
DOI: 10.1901/jeab.2002.77-171
|View full text |Cite
|
Sign up to set email alerts
|

The Generality of Selective Observing

Abstract: Four rats obtained food pellets by poking a key and 5-s presentations of the discriminative stimuli by pressing a lever. Every 1 or 2 min, the prevailing schedule of reinforcement for key poking alternated between rich (either variable-interval [VI] 30 s or VI 60 s) and lean (either VI 240 s, VI 480 s, or extinction) components. While the key was dark (mixed-schedule stimulus), no exteroceptive stimulus indicated the prevailing schedule. A lever press (i.e., an observing response), however, illuminated the ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
10

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 38 publications
1
15
0
10
Order By: Relevance
“…Specifically, the temporal distance between the S2 and the reinforcement component depends on the temporal distribution of observing responses. In Gaynor and Shull's (2002) study, an observing procedure involving the typical mixed schedule of reinforcement was used and observing responses produced the S+ or the S2 for 5 s. Gaynor and Shull found that the interstimulus interval was considerably longer during the EXT component than during the reinforce-ment component. However, this finding is not universal.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the temporal distance between the S2 and the reinforcement component depends on the temporal distribution of observing responses. In Gaynor and Shull's (2002) study, an observing procedure involving the typical mixed schedule of reinforcement was used and observing responses produced the S+ or the S2 for 5 s. Gaynor and Shull found that the interstimulus interval was considerably longer during the EXT component than during the reinforce-ment component. However, this finding is not universal.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the increases in total percentage of time spent in the schedule-correlated stimuli resulted from increases in time spent in the presence of Sϩ. Figure 2 shows the median latency between the offset of either Sϩ or SϪ and the next observing response (i.e., follow-up latencies; Gaynor & Shull, 2002). For each rat, followup latencies for observing responses preceded by the termination of Sϩ were considerably longer than those preceded by the termination of SϪ, especially at lower RR requirements.…”
Section: Conditionmentioning
confidence: 99%
“…they show selective observing of S+; see Dinsmoor 1985 for review). Similarly, Gaynor and Shull (2002) recently showed that under conditions in which competition between observing and responding for the primary reinforcer were minimized, rats showed a selective bias for observing a foodassociated S+. Dinsmoor (1983) has argued convincingly that unmeasured selective observing (i.e.…”
Section: Discussionmentioning
confidence: 88%
“…Both axes are logarithmic. Error bars represent €1 SEM methods of Gaynor and Shull (2002) to examine selective observing of a drug stimulus.…”
Section: Discussionmentioning
confidence: 99%